The relationship between train driver schedule, wellbeing, fatigue and driving performance among train driver - Nurirdina, Mohd Johan (2025)
This study looks at how train drivers' routines affect their health, how tired they are, and how well they do their job, focussing on drivers from Keretapi Tanah Melayu Berhad (KTMB). The study's goal is to find out how drivers' work plans affect their physical and mental health, as well as how well the business runs. Using a quantitative method, surveys were used to gather information about things like shift patterns, ergonomics of the workplace, rest cycles, and how tired people thought they were. There were 204 respondents who shared information about their situations and problems.Among the most important results, 59.8% of drivers said they worked shifts longer than eight hours, and 91.5% said their shift patterns were unpredictable, which made them physically and mentally tired. Also, 38.5% were unhappy with the ergonomics of their desk and said they were uncomfortable during or after their shifts. When it came to tiredness, 59.8% of drivers said they sometimes felt physically tired and 39.3% said they sometimes felt mentally tired. There were strong links (r = -0.249, p = 0.007) between shift length, tiredness, and wellbeing, which shows that schedules need to be better managed.The results show how important structured schedules, better ergonomics, and programs to help drivers deal with fatigue are for making their general working conditions better. Adding performance monitoring and mental health support tools can make operations even safer and more effective. This study gives train operators and lawmakers useful information that they can use to make the workplace safer and friendlier, which will eventually help make the railway system more reliable and long-lasting.